Tactile expectations and the perception of self-touch: an investigation using the rubber hand paradigm. - White, R; Davies, A; Halleen, T; Davies, M (2010)
The rubber hand paradigm is used to create the illusion of self-touch, by having the participant administer stimulation to a prosthetic hand while the Examiner, with an identical stimulus (index finger, paintbrush or stick), administers stimulation to the participant's hand. With synchronous stimulation, participants experience the compelling illusion that they are touching their own hand. In the current study, the robustness of this illusion was assessed using incongruent stimuli. The participant used the index finger of the right hand to administer stimulation to a prosthetic hand while the Examiner used a paintbrush to administer stimulation to the participant's left hand. The results indicate that this violation of tactile expectations does not diminish the illusion of self-touch. Participants experienced the illusion despite the use of incongruent stimuli, both when vision was precluded and when visual feedback provided clear evidence of the tactile mismatch.